Decolonization of Mining based on Qur’ānic Worldview: A Study of QS 9:34 and Mining Law in Indonesia Using Maqāṣid Syarī’ah - Baeti Rohman (Journal of Islamic Thought and Civilization, 2026)
This study examines the decolonization of Indonesia’s mining sector, highlighting how colonial structural legacies, particularly legal frameworks, have fostered the emergence of a new elite that replicates colonial power dynamics, thereby concentrating resource benefits among a select few rather than promoting collective welfare. The introduction of Government Regulation No. 25 of 2024, which grants priority rights to religious organizations for mining management, parallels the context of QS al-Taubah (9): 34, which critiques Jewish and Christian religious leaders for hoarding wealth to the detriment of communal benefit. This article employs Jasser Auda’s maqāṣid al-sharī‘ah framework to explore the Qur’ānic worldview of QS 9:34, and evalutes Indonesia’s mining laws through six principles: Qur’ānic cognition, comprehensiveness, wholeness, openness, multidimensionality, and purposefulness. This article argues that QS 9:34 emphasizes the use of wealth for the public good rather than for individual or sectarian interests.  In a postcolonial state, natural resource governance must prioritize public welfare and prevent monopolization by a small group. However, Government Regulation No. 25 of 2024 has sparked controversy due to its conflict with the Mineral and Coal Mining Law. Without equitable and transparent oversight, this policy risks harming communities and contravening the Qur’ānic worldview of justice in resource management. Consequently, the study argues that postcolonial Indonesia remains unprepared for true decolonization, as certain groups perpetuate colonial-like exploitation under various pretexts, including religious ones. Thus, on this basis, the article advocates the necessity of legal reform.